2014
DOI: 10.14245/kjs.2014.11.2.81
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary Spinal Cysticercosis: A Case Report and Review of Literature

Abstract: To report a case of spinal intramedullary cysticercosis in thoracic spine. A 47-year old man living in Korea referred to our hospital with both feet tingling sensation for about a year. Laboratory evaluations, including serologic tests were not helpful. Magnetic resonance imaging revealed a 1.7 cm intramedullary mass at T10-11 level, which believed to be a tumor instead, rather than a cysticercosis preoperatively. Successful operation was done with a histopathological result confirmed it as cysticercosis. Even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
2
0
2
Order By: Relevance
“…Extraspinal NCC constitutes vertebral NCC, whereas, intraspinal NCC comprises of epidural, subdural intramedullary and arachnoid NCC. [1,3] Intraspinal involvement by NCC is very rare with an incidence of 1.5-3.0% with intramedullary being even rarer. [1] Intramedullary lesions have significant morbidity due to limited size of spinal canal.…”
Section: Introductionmentioning
confidence: 99%
“…Extraspinal NCC constitutes vertebral NCC, whereas, intraspinal NCC comprises of epidural, subdural intramedullary and arachnoid NCC. [1,3] Intraspinal involvement by NCC is very rare with an incidence of 1.5-3.0% with intramedullary being even rarer. [1] Intramedullary lesions have significant morbidity due to limited size of spinal canal.…”
Section: Introductionmentioning
confidence: 99%
“…Поражение ЦНС наблюдается у 60-90% пациентов с ЦЗ. Выделяют церебральный и спинальный; паренхиматозный (интрамедуллярный) и экстрапаренхиматозный НЦ [6,11].…”
unclassified
“…Паренхиматозный спинальный НЦ может возникать в результате гематогенного распространения; ЦК чаще расположены на уровне хорошо васкуляризованного грудного отдела. Спинальный НЦ приводит к развитию корешкового синдрома, менингита, поперечного миелита, мышечной слабости, парапарезам, тетрапарезам, нарушению функции тазовых органов, сексуальной дисфункции, сенсорным нарушениям [6,7,10,11].…”
unclassified
“…Dear Editor, the report on "spinal neuorocysticercosis" is very interesting 1) . Kim et al reported a case and concluded that "Even though the prevalence of intramedullary spinal cysticercosis is extremely rare, and radiologic exams mimic other common tumors like ependymoma or astrocytoma, the disease should be considered as differential diagnosis 1) ." In fact, the problem of spinal cysticercosis can be sporadically seen and can be seen at any age group 2) .…”
mentioning
confidence: 99%